Enhancing The Teaching And Learning Of English For Specific Purposes (Esp) With Chatgpt - Sarah Mohammed Alsanousi Alssayah Ahmed; Ayman Riheel Alnaas Taha; Sajjad Hussain; Ali Hayat (International journal of technology and education research, 2023)
As a result of the implementation of ChatGPT into interactive learning tools for technical English, students can participate in conversational engagements that are analogous to actual engineering challenges encountered in the real world. Through this conversational interface, individual students can ask engineering-related questions, obtain accurate and useful responses via ChatGPT, and even receive comments and explanations. For example, students may question the differences between a transistor and a diode. ChatGPT can provide a response that is both precise and condensed, such as the following: